Dynamics of nicotine accumulation in Madura tobacco (Nicotiana tabacum L.): Effects of plant age and leaf position - Hidayati, Bhekti Ayu; Setiyawan, Hendrix Yulis; Pranowo, Dodyk; Dewanti, Beauty Suestining Diyah; Suprayogi, Suprayogi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Nicotine is the primary alkaloid in tobacco (Nicotiana tabacum L.), playing a significant role in determining tobacco quality. The Madura variety (Prancak 95) is highly adaptable to dryland conditions, making it suitable for studying the dynamics and rate of nicotine formation at different growth stages and leaf positions. This study aimed to measure nicotine content in Madura tobacco leaves based on plant age and leaf position and to determine its formation rate between growth phases. The experiment employed a randomized block design (RBD) with a factorial pattern, comprising plant age (i.e., 25, 40, 55, 70, and 85 days after transplanting/DAT) and leaf position (i.e., lower, middle, and upper) in three replications. Nicotine content was analyzed using the acidimetric titration method (SNI 01-7134-2006), and the formation rate was calculated as the difference in nicotine content between growth stages divided by the time interval. Results showed that nicotine content increased from 1.24% (25 DAT) to 2.72% (85 DAT). Average nicotine contents were 2.43% (upper), 1.86% (middle), and 1.64% (lower leaves). At 85 DAT, the upper leaves contained about 43% more nicotine than that of the lower leaves. The highest rate of nicotine formation occurred at 70–85 DAT.